Enhancing Science Process Skills and Learning Outcomes: The Impact of ChatGPT-Assisted Inquiry Learning on Environmental Change Education - Anis Sri Rahayu; Diana Hernawati; Dita Agustian (Universitas Islam Negeri Walisongo Semarang, 2026)
This study examined the effect of Artificial Intelligence (AI)-assisted inquiry learning on students’ science process skills and cognitive learning outcomes in environmental change material for grade X students at SMAN 1 Singaparna. The research used a quasi-experimental method with a matching-only posttest control group design. The population consisted of 12 grade X classes, and the sample was selected using purposive sampling. Research instruments included a science process skills test with 12 essay questions and a cognitive learning outcomes test with 30 validated multiple-choice questions. Data were analyzed using an independent sample t-test with SPSS. The results showed a significance value of 0.000 for both science process skills and learning outcomes, indicating that AI-assisted inquiry learning has a significant effect on students’ abilities. These findings demonstrate that ChatGPT-assisted inquiry learning positively influences science process skills and cognitive learning outcomes, making it a promising strategy for teaching environmental change topics.